The choice of antibiotic for community-acquired pneumonia - the results of a survey of doctors and an analysis of real outpatient practice - V. G. Deriushkin; A. P. Ternavskii; E. A. Ulyanova; S. V. Gatsura (Izdatelstvo OKI, 2020)
Community-acquired pneumonia (CAP) remains an urgent problem in the structure of infectious diseases worldwide including the Russian Federation. According to medical statistics the incidence rate of CAP increased by 19.1 % by December 2018 as compared to year 2017. The authors addressed the problem of rational choice of antimicrobial agents (AMAs) for outpatient treatment of this disease. The aim was to assess structure and rationality of choice of AMAs for outpatient treatment of CAP by primary care physicians in municipal outpatient clinics in Moscow. A two-stage single-center pharmacoepidemic study was conducted. The survey involved 45 primary care physicians with average age 48.5 ± 13.2 years and medical experience 22.7 ± 13.6 years. Relevant information was also copied out from 650 ambulatory records of patients receiving AMs for CAP. According to the results of our survey the leaders of the respondents' preferences are beta-lactam antibiotics - amoxicillin/clavulanate (49.0 %) followed by amoxicillin (25.5 %) and cephalosporins (15.7 %). Analysis of real clinical practice brings different picture: cephalosporins become comparable to amoxicillin/clavulanate in terms of frequency of administration, The latter significantly loses popularity, as does amoxicillin as monotherapy These data match with similar survey of 233 Moscow primary care physicians conducted earlier in 2013-2014 by one of the authors where amoxicillin/clavulanate accounted for 43.6 % of total AMAs recommendations. Thus, the initial choice of AMAs for outpatient treatment of CAP in most cases does not comply with current clinical guidelines. Physicians tend to start initial outpatient management of CAP with second-line AMAs (amoxicillin/clavulanate, cephalosporins, less commonly fluoroquinolones), underestimating macrolides and almost neglecting doxycycline. These circumstances result in unwarranted increase in drug load on the patient, decrease in safety of treatment and ineffectiveness of antimicrobial therapy in case if CAP is caused by atypical pathogens.